EKSPLORASI KERAGAMAN PLASMA NUTFAH JENGKOL DI KABUPATEN SIJUNJUNG BERDASARKAN KARAKTER MORFOLOGI - Nike Karjunita; Yeni Permata Sari; Kuswandi; Ananto (BPFP Universitas Bengkulu, 2023)
[EXPLORATION OF JENGKOL GERMPLASM’S DIVERSITY IN SIJUNJUNG REGENCY BASED ON MORPHOLOGICAL CHARACTERS]. Jengkol is one of the leading commodities in Sijunjung Regency. This research aims to determine the genetic diversity of jengkol accession in Sijunjung Regency based on morphological characters. The exploratory research was conducted in three sub-districts in Sijunjung Regency, West Sumatra from January to May 2021. The observed characters included vegetative and generative characters, which refer to the description of the registered jengkol variety. Data were analyzed using software R.3.5.2 for cluster analysis, and SPSS 17.0 for principal component analysis. The 60 accessions of jengkol from exploration in Sijunjung Regency were grouped into two main groups, namely Group 1 which consisted of two accessions, UGB 2A, and ARS 2B, while the rests belonged to Group 2. The coefficient of dissimilarity between the two groups of jengkol accessions from Sijunjung Regency about 45%, or with a similarity of 55%. The results of PCA analysis of 19 characters in 60 accessions of jengkol indicated a contribution of 79.17% of the total diversity, which was divided into seven main components. This study recommended a necessity to establish further selection from the diversity of jengkol germplasm in Sijunjung. Selected accessions can be registered by the Sijunjung Regency Government in order to increase the number of high-yielding jengkol varieties in West Sumatra, as well as be beneficial for seed breeders and farmers in this area